Advanced Data Analysis for Fluorescence-Lifetime Single-Molecule Localization Microscopy - Thiele, Jan Christoph; Nevskyi, Oleksii; Helmerich, Dominic A.; Sauer, Markus; Enderlein, Jörg (Frontiers in Bioinformatics, 2021)
Fluorescence-lifetime single molecule localization microscopy (FL-SMLM) adds the lifetime dimension to the spatial super-resolution provided by SMLM. Independent of intensity and spectrum, this lifetime information can be used, for example, to quantify the energy transfer efficiency in Förster Resonance Energy Transfer (FRET) imaging, to probe the local environment with dyes that change their lifetime in an environment-sensitive manner, or to achieve image multiplexing by using dyes with different lifetimes. We present a thorough theoretical analysis of fluorescence-lifetime determination in the context of FL-SMLM and compare different lifetime-fitting approaches. In particular, we investigate the impact of background and noise, and give clear guidelines for procedures that are optimized for FL-SMLM. We do also present and discuss our public-domain software package "Fluorescence-Lifetime TrackNTrace", which converts recorded fluorescence microscopy movies into super-resolved FL-SMLM images.